NTEGRATED NUTRIENT MANAGEMENT EFFECT ON YIELD AND QUALITY OF BRINJ ALITY OF BRINJAL (Solanum melongenal Solanum melongenal Solanum melongenal L.) - SINGH, MANPREET; THAKUR, ANURADHA (The Bioscan, 2018)
An experiment with the effect of integrated nutrient management on the yield of brinjal was conducted. Among different levels of fertilizers in combination with organic manures and biofertilizers the maximum plant height (95.17 cm), plant spread (83.49 cm), days to 50 per cent flowering (41.78), days to first picking (61.22), fruit diameter (81.57 mm), number of fruits per plant (11.49), fruit yield per plant (2.31 kg), fruit yield per hectare(54.55 t ha-1), shelf life (8.67 days), TSS (5.17°Brix), average fruit weight (196.20 g) and fruit length (102.30 mm) were recorded with the combined application of 75 per cent RDF + biofertilizers + farm yard manure.These results suggested that the optimum production of brinjal can be obtained with integrated application of 75 per cent RDF + farm yard manure + biofertilizers. The use of biofertilizers along with organic manures (FYM) with the reduced quantity of chemical fertilizers is therefore recommended for better yield of brinjal